2013
DOI: 10.3389/fpsyg.2013.00641
|View full text |Cite
|
Sign up to set email alerts
|

Charting the role of the number line in mathematical development

Abstract: Individuals who do well in mathematics and science also often have good spatial skills. However, the predictive direction of links between spatial abilities and mathematical learning has not been firmly established, especially for young children. In the present research, we addressed this issue using a sample from a longitudinal data set that spanned 4 years and which includes measures of mathematical performance and various cognitive skills, including spatial ability. Children were tested once in each of 4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
82
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 34 publications
12
82
2
4
Order By: Relevance
“…It was also observed that there were medium to strong significant correlations between all visuo-spatial and visuo-motor integration measures and number line estimation, barring between R 2 LIN and both visuo-spatial working memory and mental rotation. Therefore, these data highlight the important relationship between visuo-spatial processing, visuo-motor integration skills and number line estimation and replicate previous research by both LeFevre et al (2013) and Crollen and Noël (2015).…”
Section: Creation Of Component Variables From Visuo-motor Integrationsupporting
confidence: 90%
See 3 more Smart Citations
“…It was also observed that there were medium to strong significant correlations between all visuo-spatial and visuo-motor integration measures and number line estimation, barring between R 2 LIN and both visuo-spatial working memory and mental rotation. Therefore, these data highlight the important relationship between visuo-spatial processing, visuo-motor integration skills and number line estimation and replicate previous research by both LeFevre et al (2013) and Crollen and Noël (2015).…”
Section: Creation Of Component Variables From Visuo-motor Integrationsupporting
confidence: 90%
“…However, hierarchical regressions indicated that PAE, but not R 2 LIN , was a significant predictor of mathematical achievement over and above visuo-spatial and visuo-motor integration scores. LeFevre et al (2013) observed that number line estimation performance (albeit as measured by linear slope values between to-be-estimated and actual estimates) was not an independent predictor of mathematical achievement after accounting for visuo-spatial skills, and the current study has replicated this finding using R 2 LIN values.…”
Section: Creation Of Component Variables From Visuo-motor Integrationsupporting
confidence: 60%
See 2 more Smart Citations
“…With respect to cross-domain influences LeFevre et al (2013) showed a reliable impact of children's spatial abilities on numerical skills. Additionally, Durkin et al (2013) observed that language ability is a unique predictor of actual and future numerical achievement.…”
mentioning
confidence: 99%